Sliding Mode Disturbance Observer-Based Control of a Laboratory Twin Rotor Multi Input-Multi Output System - Seyyed Sajjad Moosapour; Habib Mehdipour; Mehrdad Keramatzadeh (IEEE Access)
This paper deals with the development, modeling, identification, and robust control of a twin-rotor MIMO system (TRMS). The TRMS is a two rotational degree-of-freedom unstable structure with significant channel-coupling, nonlinear characteristics, and external disturbances, which resembles a real helicopter’s characteristics and can be used as an aerodynamic testing setup. The coupled nonlinear state-space representation of the developed TRMS is obtained, and model parameters are identified. The identified model is validated using different experimental test scenarios. To estimate the lumped uncertainty including cross-coupling effects and external disturbances, a novel finite-time sliding mode disturbance observer is proposed. Based on the presented disturbance observer, a finite-time sliding mode controller is designed for the coupled identified TRMS. Performance evaluation of the presented observer-based controller is demonstrated through a series of experiments and simulations. The robustness of the proposed scheme is shown. Moreover, an average improvement of approximately 20% in system performance, as measured by the reduction in the Integrated Squared Error (ISE), is observed compared to the PID controller.